2007
DOI: 10.1128/ec.00167-07
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Elongation and Gene Expression inChlamydomonas reinhardtii

Abstract: Lithium (Li

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
(66 reference statements)
3
12
0
Order By: Relevance
“…Similar treatment of RNAi strains did not show apparent length difference. It has been reported that longer treatment of cells induces formation of bulbed flagella at the flagellar tip, and the flagella begin to curl at the base forming big “bulbs” which are eventually lost forming aflagellate cells [52], [53]. We have confirmed this observation, as shown in Figure 6B and C.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar treatment of RNAi strains did not show apparent length difference. It has been reported that longer treatment of cells induces formation of bulbed flagella at the flagellar tip, and the flagella begin to curl at the base forming big “bulbs” which are eventually lost forming aflagellate cells [52], [53]. We have confirmed this observation, as shown in Figure 6B and C.…”
Section: Resultssupporting
confidence: 88%
“…Inhibition of GSK3β [52] or adenylate cyclase [51] has been proposed to underlie the effect of LiCl. Treatment of Chlamydomonas wild type cells with 25 mM LiCl induced about 40% increase of flagellar length from 12 µm to 17 µm similarly as reported (Figure 6A) [53]. Similar treatment of RNAi strains did not show apparent length difference.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Although LiCl induces flagellar growth (Nakamura et al , 1987; Periz et al , 2007), little growth occurs in the time during which IFT is recorded and 20 mM LiCl does not induce changes in the rate or frequency of anterograde or retrograde IFT (Dentler, 2005). Used cautiously, addition of 10–20 mM LiCl can facilitate recording IFT in motile flagella.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative genomic analysis (Avidor-Reiss et al, 2004;Chen et al, 2006;Li et al, 2004); transcriptional profiling (Blacque et al, 2005;Choksi et al, 2014;Periz et al, 2007;Stolc et al, 2005); and proteomic studies from Chlamydomonas flagella (Pazour et al, 2005), primary cilia (Ishikawa et al, 2012), motile cilia (Narita et al, 2012), and specialized mammalian cilia (Liu et al, 2007;Mayer et al, 2009) have identified numerous kinesin molecules. In addition, functional studies have discovered additional kinesins that are not identified in those large-scale analyses.…”
Section: Flagellar and Ciliary Kinesinsmentioning
confidence: 99%